2018
DOI: 10.1021/acs.molpharmaceut.8b00515
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Gastrointestinal Behavior of Ibuprofen with the Systemic Exposure between and within Humans—Part 1: Fasted State Conditions

Abstract: The goal of this project was to explore and to statistically evaluate the responsible gastrointestinal (GI) factors that are significant factors in explaining the systemic exposure of ibuprofen, between and within human subjects. In a previous study, we determined the solution and total concentrations of ibuprofen as a function of time in aspirated GI fluids, after oral administration of an 800 mg IR tablet (reference standard) of ibuprofen to 20 healthy volunteers in fasted state conditions. In addition, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The hydrodynamics of the GI lumen are dynamic and dependent on the amount of fluid present and the contractile activity of the muscles surrounding the GI lumen. , It is hypothesized that the ABLs surrounding dissolving particles and the GI lumen within these water pockets are significant barriers to dissolution and absorption for certain poorly soluble APIs. Furthermore, it is expected that the hydrodynamics of these fluid pockets will vary locally and may yield a distribution of ABL thicknesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrodynamics of the GI lumen are dynamic and dependent on the amount of fluid present and the contractile activity of the muscles surrounding the GI lumen. , It is hypothesized that the ABLs surrounding dissolving particles and the GI lumen within these water pockets are significant barriers to dissolution and absorption for certain poorly soluble APIs. Furthermore, it is expected that the hydrodynamics of these fluid pockets will vary locally and may yield a distribution of ABL thicknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is expected that the hydrodynamics of these fluid pockets will vary locally and may yield a distribution of ABL thicknesses. In a study evaluating the intersubject variability exposure of ibuprofen, a BCS Class II drug, Amidon and co-workers have identified the variability to be a result of motility differences across subjects. , It has been suggested that slower transit times due to lower contractile activity could lead to decreased agitations of the ABLs surrounding dissolving particles . Therefore, for poorly soluble drugs whose permeability is limited by the transport through the ABL, it is expected that the sensitivity to nanospeciation would be significant. , …”
Section: Discussionmentioning
confidence: 99%
“…Immediate-release (IR) orally administered drug products need to be first dissolved in the gastrointestinal (GI) tract and then be absorbed through the small intestine’s epithelial cell membrane to reach systemic circulation. , According to the biopharmaceutics drug classification system (BCS), dissolution is the rate-limiting process for the oral delivery of BCS class II drugs with low solubility and high permeability . The in vivo dissolution rate of drug products is governed by drug properties such as p K a , intrinsic solubility, and particle size, in addition to the physiological parameters such as gastric emptying rate, hydrodynamic conditions generated due to the intestinal motility, buffer species, buffer capacity, ionic strength, bile salts, and pH .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, all the systemic availability events of CellCept are controlled by GE ibuprofen. 39 In addition, it has been experimentally demonstrated that delayed GE was associated with a longer T max and lower C max , but the total exposure to MPA was not affected. 24 More GI dynamics get involved under fed conditions due to the significantly slower dissolution rate in the elevated pH range.…”
Section: ■ Discussionmentioning
confidence: 99%